A maradványhallás megőrzésének lehetőségei cochlearis implantáció során Nucleus CI532 Slim Modiolar elektródasorral = Possibilities for residual hearing preservation with Nucleus CI532 Slim Modiolar electrode array. Case report - Nagy Roland; Jarabin János András; Dimák Balázs; Perényi Ádám; Tóth Ferenc; Szűts Viktória; Jóri József; Kiss József Géza; Rovó László (2018)
During the rehabilitation of hearing-impaired patients, the preservation of residual acoustic hearing following cochlear implantation by minimizing the implantation trauma allows for improved hearing performance. To achieve this, minimally invasive, soft surgery methods and thinner, atraumatic electrodes were required. In our present study, we reported a case where Cochlear® Nucleus CI532 Slim Modiolar electrode was implanted in a patient with residual hearing. Our aim was to study the possible preservation of postoperative acoustic residual hearing by audiological monitoring. Since childhood, due to her congenital hearing loss, she has been wearing a conventional, airborne hearing correction device on both ears. Six months before cochlear implantation, we measured the progression on both sides of the hearing loss, so we decided to perform cochlear implantation. The patient had residual hearing on both ears prior to surgery thus the Cochlear® Nucleus CI532 Slim Modiolar Implant was used. The minimally invasive surgery was performed on the patient's right ear through the round window approach. Compared to the preoperative hearing threshold (average 85 dBHL) in the 4th postoperative week, an initial hearing threshold progression of 20-25 dBHL was observed between 0.25 and 1.0 kHz, while of 5-10 dBHL between 2.0-4.0 kHz. Hearing threshold measured in the 6th month showed a slight progression in the range above 1 kHz, but improved by the 12th month, to the results achieved at the 4th week. The effects of cochlear implantation on residual hearing have been studied in numerous studies, in which several key surgical and technical factors have been identified. Nucleus CI532 is a Slim Modiolar electrode profile that is close to the modiolus, so it is expected to have a lower endocochlear hydrodynamic load since it lies in the covering of the osseus spiral lamina, thus less influencing the dynamics of the basilar membrane. However, the perimodiolar location of the electrode array allows the adjacent nerve elements of the spiral ganglion to be stimulated with a lower electrical intensity and a reduced surface that may be neuroprotective. Preservation of acoustic residual hearing following cochlear implantation improves the patient's speech perception and the sound localization skills, particularly in difficult circumstances. Long-term residual hearing preservation may also be of great importance in the subsequent feasibility for regenerative procedures and drug treatments. Orv Hetil. 2018; 159(41): 1680-1688.